Academic Stress and Coping Strategies of High School Students with Single-Parents - Kenia Hukom; Dennis V. Madrigal (Philippine Social Science Journal, 2020)
Today, stress is growing day by day among students with single-parents, yet the basic concepts to minimalize, endure, and master the stress are often ignored.  In many places around the world, students experience significant academic distress, and being unaware of how to deal with it is a serious concern, which worsens the school-setting situation. Education and social support systems are prime movers in developing and enriching students, particularly in adopting appropriate coping strategies. Hence, this paper describes the level of academic stress and the extent of coping strategies of high school students with single-parents in a Catholic School in Antique during the school year 2019-2020.  Likewise, it explores the relationship existing between the students' demographics and their academic stress and coping strategies.